PUSAT KUCING JATINEGARA DENGAN PENDEKATAN URBAN AKUPUNKTUR - Putri Nurandini; Timmy Setiawan (Jurnal Sains, Teknologi, Urban, Perancangan, Arsitektur (Stupa), 2023)
Physical degradation in the Jatinegara animal market area can be seen from the stalls that occupy the sidewalks. As a result, the sidewalks become dirty, smelly, and damp because animal waste is also jammed, causing pedestrians and motorists to suffer. Acupuncture urban planning is carried out to produce impact and quality for large scale urban areas by producing a chain reaction, where one project or design made at one point can have an impact or positive effect on other areas. Macro, meso, micro analyzes were carried out to understand more about the Jatinegara Animal Market. Data collection was taken from print media, interviews and observations. The design method uses an urban acupuncture approach. In the Jatinegara Animal Market area, several issues were found in the animal market area, namely the stalls of traders who eat the pedestrian street, so that it becomes dirty and slippery and causes traffic jams. The concept of "Architecture for Animals and Humans", Jatinegara Cat Center is a forum for the pet trade, requiring comfortable buildings that can bring out the original characters of the pets being sold. Keywords:  Degradation; urban acupuncture; architecture for animal and human Abstrak Degradasi fisik pada kawasan pasar hewan Jatinegara dapat dilihat dari kios-kios yang menempati trotoar akibatnya trotoar menjadi kotor, bau, lembab karena kotoran hewan dan juga macet sehingga pejalan kaki dan pengendara terganggu. Penataan urban Akupunktur dilakukan untuk menghasilkan dampak dan kualitas bagi lingkup skala kota yang besar dengan menghasilkan reaksi berantai (chain react), dimana dari satu proyek atau rancangan yang dibuat di satu titik dapat memberikan pengaruh atau efek positif bagi area lainnya. Analisis makro, meso, mikro dilakukan untuk memahami lebih lanjut mengenai Pasar Hewan Jatinegara. Pengumpulan data diambil dari media cetak, wawancara dan observasi. Metode perancangan menggunakan pendekatan urban akupuntur. Kawasan Pasar Hewan Jatinegara, ditemukan beberapa isu di kawasan pasar hewan yaitu kios-kios pedagang yang memakan jalan pedestrian, sehingga menjadi kumuh dan licin dan menimbulkan kemacetan. Konsep "Architecture for Animal and Human", Jatinegara Cat Center merupakan sebuah wadah untuk perdagangan hewan peliharaan, membutuhkan kenyamanan bangunan yang dapat memunculkan karakter asli dari hewan peliharaan yang dijual.